Kidney Bean Substitution Ameliorates the Nutritional Quality of Extruded Purple Sweet Potatoes: Evaluation of Chemical Composition, Glycemic Index, and Antioxidant Capacity - Eny Palupi; Nira Delina; Naufal M. Nurdin; Hana F. Navratilova; Rimbawan Rimbawan; Ahmad Sulaeman (Foods, 2023)
The extrusion process may influence the nutritional profiles of carbohydrate-rich food ingredients, including the glycemic index (GI) and antioxidant capacity. This study aimed to evaluate the nutritional profile of extruded purple sweet potato (EPSP) substituted with kidney bean flour (KBF) (0, 30, and 40%). These foods were further characterized by their proximate composition, resistant starch, polyphenols, GI, and antioxidant capacities. The 40% KBF substitution enhanced the protein and fiber contents of the EPSP by up to 8% and 6%, respectively. Moreover, it also revealed that EPSP with 40% KBF substitution had a low-GI category (53.1), while the 0 and 30% substitution levels had a high-GI category, i.e., 77.4 and 74.7, respectively. However, the extrusion processing reduced the anthocyanin content and antioxidant capacity of purple sweet potato flour containing 40% KBF by 48% and 19%, respectively. There was a significant relationship between the GI values of proteins, fats, and fibers (p < 0.05). The insignificant effect of resistant starch and phenol contents on GI value was recorded due to the low concentrations of those components. KBF substitution could ameliorate the profile of protein, fiber, and GI, but not for antioxidant capacity. The other innovative processes for preserving antioxidant capacity might improve the product quality.